1982
DOI: 10.1093/geronj/37.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Lecithin and Memory Training in Suspected Alzheimer's Disease

Abstract: Ten patients diagnosed clinically as having Alzheimer's disease (age range 54 to 73 years) were given 35 g/day of a 53% lecithin mixture for two weeks, in a double-blind crossover design. Patients received memory training during the lecithin condition and "placebo training" during the placebo drug condition. Repeated assessment with Buschke's Selective Reminding Procedure provided no evidence of a therapeutic lecithin effect either during the two week clinical trial or during longer follow-up trials. Noninvasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There is also some evidence that dietary choline can improve some of the motor symptoms of tardive dyskinesia that develop as a side effect of neuroleptic drugs (Davis, Berger, & Hollister, 1975;Gelenberg, Doller-Wojcik, & Growdon, 1979;Growdon, Hirsch, Wurtman, & Weiner, 1977). In contrast, many investigations have found dietary choline to be ineffective (such as Brinkman et al, 1982;Davis et al, 1980;.…”
Section: Discussionmentioning
confidence: 99%
“…There is also some evidence that dietary choline can improve some of the motor symptoms of tardive dyskinesia that develop as a side effect of neuroleptic drugs (Davis, Berger, & Hollister, 1975;Gelenberg, Doller-Wojcik, & Growdon, 1979;Growdon, Hirsch, Wurtman, & Weiner, 1977). In contrast, many investigations have found dietary choline to be ineffective (such as Brinkman et al, 1982;Davis et al, 1980;.…”
Section: Discussionmentioning
confidence: 99%
“…Modest improvements were observed compared with placebo in several memory tests (71,73). However, there are studies in which the choline effect on memory was not observed in normal subjects (36,48,89) or in patients with dementias (15,42,147).…”
Section: Choline and Neuronal Function In Adultsmentioning
confidence: 98%
“…The elderly (Cohen et al 1995) or patients with Alzheimer's disease (Nitsch et al 1992) have reduced levels of free choline and PC in the brain. Some (Alvarez et al 1997;Ladd et al 1993;Levy 1982;Little et al 1985;Sitaram et al 1978;Spiers et al 1996) but no all (Brinkman et al 1982;Drachman et al 1982;Fitten et al 1990;Harris et al 1983;Mohs and Davis 1980;Weinstein et al 1991) studies including healthy or demented individuals reported improved performance on memory and learning tasks following supplementation with choline, CDP-choline, or PC. A limited number of individuals (n=9-95) was included in these studies.…”
Section: Choline and The Human Central Nervous System Development Andmentioning
confidence: 99%